Taxonomy of Dianthus (Caryophyllaceae): overall phylogenetic relationships and assessment of species diversity based on a first comprehensive checklist of the genus - Fassou, Georgia; Korotkova, Nadja; Nersesyan, Anush; Koch, Marcus; Dimopoulos, Panayotis; Borsch, Thomas (PhytoKeys, 2022)
In this study, we present an overall phylogenetic framework for Dianthus using four plastid regions (matK-trnK-psbA, rpl32-trnL, trnQ-rps16) and nuclear ITS and a species-level checklist for the genus developed by using all available databases and the literature. The trees from the plastid dataset depict a clade of Dianthus that also includes Velezia and a few taxa of Petrorhagia. New combinations in Dianthus are provided for these species. The checklist of Dianthus in this new delimitation covers 1781 names, with 384 accepted species, 150 subspecies, 12 heterotypic varieties and two forms (not counting autonyms), 1050 synonyms, 22 hybrid names and 172 unresolved names, 3 names were excluded. Implications for the evolution of flower characters, life forms, biogeography, as well as sectional classification are discussed based on the phylogenetic framework.
Gesehen am 13.07.2022